Facilitation method for the translation of biological systems to technical design solutions. Issue 3 (2nd October 2018) - Weidner, Bradley V.; Nagel, Jacquelyn; Weber, Hans-Joachim
Abstract: Innovative designs can be limited by the experience and knowledge of the individual designers. These limitations can be combated by integrating knowledge from other fields of study. However the vernacular used by the respective fields creates a gap, which requires a process of facilitated translation to bridge. Specifically, biology is a field that has been used for inspiration for design solutions by engineers. This field, also known as biomimicry, has already proven to be a successful tool for identifying innovative inspiration for design but is under-utilized due to the difficulty of translating between biology and engineering. The proposed bioinspired design process discussed in this paper uses sketching of biological systems to create visual analogies that facilitate the translation from a biological system to technical design solution. Sketching of the inspiring biological system re-conceptualizes the information to aid in comprehension as well as establishes a clear path to cross-domain analogy identification to result in by innovative technical design solutions. This paper focuses on the theory underlining the proposed bioinspired design process, and as such, reviews existing literature to identify the opportunity, states the supporting evidence, and presents the approach for addressing the opportunity with an example and a case study to demonstrate applicability.